Embryo-larval exposure to atrazine reduces viability and alters oxidative stress parameters in Drosophila melanogaster. - Figueira, F.H.; Aguiar, L.M.; Rosa, C.E. (Comparative biochemistry and physiology. Toxicology & pharmacology : CBP, 2017)
The herbicide atrazine has been used worldwide with subsequent residual contamination of water and food, which may cause adverse effects on non-target organisms. Animal exposure to this herbicide may affect development, reproduction and energy metabolism. Here, the effects of atrazine regarding survival and redox metabolism were assessed in the fruit fly D. melanogaster exposed during embryonic and larval development. The embryos (newly fertilized eggs) were exposed to different atrazine concentrations (10?M and 100?M) in the diet until the adult fly emerged. Pupation and emergence rates, developmental time and sex ratio were determined as well as oxidative stress parameters and gene expression of the antioxidant defence system were evaluated in newly emerged male and female flies. Atrazine exposure reduced pupation and emergence rates in fruit flies without alterations to developmental time and sex ratio. Different redox imbalance patterns were observed between males and females exposed to atrazine. Atrazine caused an increase in oxidative damage, reactive oxygen species generation and antioxidant capacity and decreased thiol-containing molecules. Further, atrazine exposure altered the mRNA expression of antioxidant genes (keap1, sod, sod2, cat, irc, gss, gclm, gclc, trxt, trxr-1 and trxr-2). Reductions in fruit fly larval and pupal viability observed here are likely consequences of the oxidative stress induced by atrazine exposure.